Abundant fluids in southern Kumano Basin linked to fluid source and slow earthquakes at the plate boundary in the Nankai Trough - Xin Liu; Ayako Nakanishi; Gou Fujie; Takashi Tonegawa; Yasuyuki Nakamura; Koichiro Obana; Shuichi Kodaira (Proceedings of the National Academy of Sciences, 2025)
The Nankai Trough is a major subduction zone in southern Japan capable of generating the next M7 or larger earthquake off Kii Peninsula. In addition to earthquakes characterized by sharp P and S arrivals, there are numerous slow earthquakes without clear P phases at the subducting plate boundary corresponding to transient slips that are related to fluids at the plate boundary and high pore pressure. In this study, we perform ambient noise differential adjoint tomography to derive the S-wave velocity model beneath a linear Ocean Bottom Seismometer (OBS) array, which was previously difficult based on airgun active source study. We find that S-wave velocities in the southern (seaward) Kumano Basin are significantly lower than in the northern (landward) Kumano Basin, suggesting weak upper plate and abundant fluids in the southern Kumano Basin. The fluid-rich southern Kumano Basin lies above a weak interplate coupling zone with shallow slow earthquakes and pressurized fluids due to plate interface dehydration. Conversely, the northern Kumano Basin overlies a strong interplate coupling zone with few slow earthquakes, suggesting fluid migration from the weak-coupling interface to the forearc basin above.